2014
DOI: 10.1080/14733145.2012.758754
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy for depression: Coping style matters

Abstract: Aim: The finding by Jacobson and colleagues that there was no difference in treatment outcome for individuals treated with a complete cognitive therapy (CT) package and those receiving behavioural activation raised serious concerns about the mediational role of cognition in depression. The present study was designed to test whether the interaction between coping and cognition predicts changes in depressive symptomatology. Method: The sample (N=30) was derived from the full CT condition of the study conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The measure has been used in numerous studies and its validity and reliability are well established [22][23][24][25][26][27][28][29][30]. The rating scale comprises 12 categories of coping originating from a landmark study conducted by Skinner and colleagues [31].…”
Section: Methodsmentioning
confidence: 99%
“…The measure has been used in numerous studies and its validity and reliability are well established [22][23][24][25][26][27][28][29][30]. The rating scale comprises 12 categories of coping originating from a landmark study conducted by Skinner and colleagues [31].…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta‐analysis of 99 studies revealed that the “Big Five” personality dimensions (extraversion, agreeableness, conscientiousness, neuroticism, and openness – also called intellect/imagination) were associated with a wide range of therapeutic outcomes, including decrease in symptomatology, creation of a working alliance, and satisfaction with therapy (Bucher et al, 2019). Similarly, coping style has been shown to be a predictor of treatment outcome for those with psychiatric disorders (Beutler et al, 2018; Davies et al, 2011; Demmel & Rist, 2005; Kommescher et al, 2016; Renaud et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of that fact that the popular media has often vilified particular “problem” genres of music such as metal and rap (Lozon & Bensimon, 2014; Powell et al, 2021), research has demonstrated that the effects of music listening on mental health are contingent upon the individual’s coping style (Horwitz et al, 2018; Renaud et al, 2014) and cognitive awareness (Garrido et al, 2019; Stewart et al, 2019). Music is not always used effectively by people experiencing depression, which is associated with high levels of maladaptive coping (Renaud et al, 2014) including emotion-oriented (Miranda & Claes, 2008) and ruminative coping (Garrido et al, 2019; Stewart et al, 2019) as well as avoidant coping (McFerran & Saarikallio, 2014; White Hughto et al, 2017). Those with a ruminative coping style—which is highly predictive of clinical depression—display higher interests in listening to music that can intensify depression symptomatology (Garrido & Schubert, 2013).…”
mentioning
confidence: 99%